Organic complexation of copper in throughfall and open field bulk deposition: Influence of the tree canopy of Mediterranean forest ecosystems. (January 2017) - Karavoltsos, Sotirios; Fotiadis, Fotios; Michopoulos, Panagiotis; Sakellari, Aikaterini; Plavšić, Marta; Bourletsikas, Athanassios; Kaoukis, Kostas; Thomaidis, Nikolaos S.; Dassenakis, Manos; Scoullos, Michael
Abstract: The complexing capacity for Cu ions ( L T ) and the apparent stability constant values (log K app ) were measured in throughfall (TF) and open field bulk deposition (BD), at two Mediterranean forest ecosystems of western Greece. L T was measured for the first time in the TF of natural forests. Concentrations of L T were three-to-four-fold higher in TF (mean ± st.dev: 2014 ± 769 nM for Varetada and 1565 ± 595 nM for Karpenissi) compared to those in BD (531 ± 517 nM and 468 ± 321 nM, respectively). In all TF and BD samples, L T concentrations were significantly higher than the corresponding total Cu concentrations, indicating that Cu was fully complexed. The L T /TOC ratios in TF were found comparable between the two study sites (235 ± 149 nM mg −1 C for Varetada and 256 ± 233 nM mg −1 C for Karpenissi) and with those of BD (226 ± 257 and 163 ± 163 nM mg −1 C, respectively). The determined mean log K app values were almost identical in TF (6.8 ± 0.7 at Varetada; 6.8 ± 0.6 at Karpenissi) and BD (6.5 ± 0.6 at Varetada; 6.8 ± 0.3 at Karpenissi), pointing to the fact that regardless of the enrichment of TF in ligands ( L T (TF)  >  L T (BD) ) the type of binding sites remain the same. The log K app values which were obtained herewith are similar to those obtained for humic-like substances (HULIS), indicating them as the most widespread type of ligands in BD and TF. Graphical abstract: Highlights: Cu complexation in forest throughfall was studied for the first time by DPASV. Samples were collected from two different Mediterranean forest ecosystems. In throughfall (TF) and bulk deposition (BD) copper was fully complexed. Cu ligands concentrations were determined 3–4 fold higher in TF than in BD. HULIS seem to be the most widespread type of ligands in both type of precipitations.